(untitled) (Journal of Renal and Hepatic Disorders, 2024)
Background: Membranous nephropathy (MN) is a glomerular disease commonly presenting as a nephrotic syndrome in adults. Various immunosuppressive medications have been used in the treatment of the same with different levels of success. Hence we have undertaken a retrospective analysis of “Clinical profile, response and outcome of various immunosuppressive regimens used for treatment of membranous nephropathy” to determine the efficacy of each treatment regimen. Methods: A retrospective observational cohort study was conducted in a single tertiary care centre in southern India. Patients with proven primary membranous nephropathy from 2010 to June 2020 with a minimum duration of follow-up of one year and treated with different immunosuppressive regimens were included in the study. Results: The total number of patients in the study was 129. Mean age of onset was 39 years with a follow-up of a minimum of 1 year and a maximum of 10 years, the mean follow-up being 3 years. 46.5% achieved complete remission, 23.3% had partial remission and 10.9% had relapse, doubling of serum creatinine was seen in 5 (3.9%) and chronic kidney failure requiring kidney replacement therapy in 3 (2.3%) respectively. Presence of interstitial fibrosis and tubular atrophy (IFTA) had a significant correlation p-value 0.02, patients with IFTA less than 30% performed the best with 54/71 patients (60%) achieving remission. Conclusions: Hypertension and IFTA at presentation were predictors for worse outcomes. modified Ponticelli, followed by rituximab, were the most effective in inducing and maintaining remission.